1987
DOI: 10.1007/bf00541378
|View full text |Cite
|
Sign up to set email alerts
|

Studies of pharmacokinetics and therapeutic effects of glucocorticoids entrapped in liposomes after intraarticular application in healthy rabbits and in rabbits with antigen-induced arthritis

Abstract: Dexamethasone palmitate (DMP) entrapped in liposomes of defined sizes was administered intraarticularly in healthy rabbits and in rabbits with antigen-induced arthritis. The pharmacokinetics and therapeutic effect of liposomal DMP were measured and compared with corresponding experiments using microcrystalline triamcinolone acetonide (TAC). The small DMP liposomes (diameter 160 nm) showed a greater decrease in joint circumference than the 3-times-higher dose of microcrystalline TAC. Moreover, about 98% of admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…This was supported by a study by Bonanomi et al [13], wherein the synovial retention of the liposomes improved on increasing their size. This was supported by a study by Bonanomi et al [13], wherein the synovial retention of the liposomes improved on increasing their size.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…This was supported by a study by Bonanomi et al [13], wherein the synovial retention of the liposomes improved on increasing their size. This was supported by a study by Bonanomi et al [13], wherein the synovial retention of the liposomes improved on increasing their size.…”
mentioning
confidence: 62%
“…The size of liposomes was found to affect the pharmacokinetics and therapeutic effect of the entrapped dexamethasone palmitate when administered intra-articularly in rabbits with antigen induced arthritis [13]. The larger sized liposomes (diameter 750 nm) were found to be more effective than the smaller ones (diameter 160 nm) which, in turn, were found to be more effective than the free drug.…”
Section: Dexamethasone Palmitatementioning
confidence: 99%
See 1 more Smart Citation
“…It was also observed that about 36% of the liposomal dexamethasone palmitate was still in the synovial fluid after 6 h of injection while triamcinolone acetonide had fully disappeared from the joints till that time. Increase in diameter of liposomal vesicles was shown to improve the retention time of drug [96]. …”
Section: Drug Delivery Systems For Ra Therapymentioning
confidence: 99%
“…Dex-liposomes, reported as early as the late 1980s (50), have been evaluated in numerous acute and chronic conditions. In models of ALI, pretreatment of animals with liposomal Dex inhibited granulocyte influx and inflammatory mediator expression as well as (51) or even better than (52) treatment with the free drug.…”
Section: Nanocarrier-mediated Delivery Of Anti-inflammatory Agentsmentioning
confidence: 99%